The Involvement of Descending Pain Inhibitory System in Electroacupuncture-Induced Analgesia - Lv, Qiuyi; Wu, Fengzhi; Gan, Xiulun; Yang, Xueqin; Zhou, Ling; Chen, Jie; He, Yinjia; Zhang, Rong; Zhu, Bixiu; Liu, Lanying (Frontiers in Integrative Neuroscience, 2019)
Chronic pain is a major health problem, which would impair life quality and reduce productivity. Electroacupuncture (EA), a modality of medicine based on the theories of Traditional Chinese Medicine, presents great therapeutic effects on chronic pain. The clinic application has gained increasing popularity, and in parallel, more researches have been performed on the mechanisms of EA-induced analgesia. The past decades have seen enormous advances both in neuronal circuitry of needle-insertion and in its molecular mechanism. EA blocks pain by activating the descending pain inhibitory system, which originates in the brainstem and terminates at the spinal cord. This review synthesizes corresponding studies to elucidate how EA alleviate pain via the mediation of this descending system. Much emphasis has been put on the implication of descending serotonergic and noradrenergic pathways in the process of pain modulation. Also, other important transmitters and supraspinal regions related to analgesic effects of EA has been demonstrated. Finally, it should be noticed that there exists some shortcomings involved in the animal experimental design for EA, which account for conflicting results obtained by different studies.